Aspectos da complexidade gramatical: uma contribuição para o ensino - Costa, Maria Aurora Rocha (1997)
This work evaluates the grammatical complexity of a set of 116 compositions, the task being proportionately distributed among students of the 4th and 8th grades, and those in the 2nd years of highschool, together with 160 texts from Portuguese, Science and Social Studies textbooks, correspounding to the same school levels. Grammatical complexity involves the aspects of lexical density and the degree of syntactic complexity which a text presents. The level of lexical density, according to Halliday's suggestion, is obtained from the ratio between the number of lexical items, with their own weights, and the total number of clauses in a text. Grammatical complexity is measured by the application of a sequence of formulae involving clause length, t-unit lengths, t-unit coordination index and subordination coefficient, aiming not only at the measurement of sentence length, but also the characterization of mechanisms through which sentences are lengthened. This research tests general hypotheses affirming that texts produced by students belonging to the three school levels in study do not reach the syntactic maturity standard pointed out by Hunt and do not distinguish very much as far as lexical density is concerned; that texts from textbooks differ substantially from student's texts as far as grammatical complexity as a whole is concemed. The results show that the syntactic maturity level does not develop in a11indexes from a grade to another, and that only in some disciplines do the texts from textbooks differ significantly from those produced by students.